Update on ocular manifestations of the main monogenic and polygenic autoinflammatory diseases - Fonollosa, Alex; Carreño, Ester; Vitale, Antonio; Jindal, Ankur K.; Ramanan, Athimalaipet V.; Pelegrín, Laura; Santos-Zorrozua, Borja; Gómez-Caverzaschi, Verónica; Cantarini, Luca; Fabiani, Claudia; Hernández-Rodríguez, José (Frontiers in Ophthalmology, 2024)
Autoinflammatory diseases include disorders with a genetic cause and also complex syndromes associated to polygenic or multifactorial factors. Eye involvement is present in many of them, with different extent and severity. The present review covers ophthalmological lesions in the most prevalent monogenic autoinflammatory diseases, including FMF (familial Mediterranean fever), TRAPS (TNF receptor-associated periodic syndrome), CAPS (cryopyrin-associated periodic syndromes), Blau syndrome, DADA2 (deficiency of adenosine deaminase 2), DITRA (deficiency of the interleukin-36 receptor antagonist), other monogenic disorders, including several ubiquitinopathies, interferonopathies, and the recently described ROSAH (retinal dystrophy, optic nerve edema, splenomegaly, anhidrosis, and headache) syndrome, and VEXAS (vacuoles, E1 enzyme, X-linked, autoinflammatory, somatic) syndrome. Among polygenic autoinflammatory diseases, ocular manifestations have been reviewed in Behçet’s disease, PFAPA (periodic fever, aphthous stomatitis, pharyngitis and cervical adenitis) syndrome, Still’s disease and autoinflammatory bone diseases, which encompass CRMO (chronic recurrent multifocal osteomyelitis) and SAPHO (synovitis, acne, pustulosis, hyperostosis and osteitis) syndrome.